2013
DOI: 10.4102/curationis.v36i1.78
|View full text |Cite
|
Sign up to set email alerts
|

Lived experiences of a community regarding its involvement in a university community-based education programme

Abstract: The researched community indeed benefited in its participation in the University Nursing School (UNS) CBE programme. However, there is a need to improve the communication between partners to make the partnership more sustainable through close relationships and interaction. There is also a need for further research on related aspects of the community's involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…[6,8,36,53] Linda et al [8] used an interpretive existentialistphenomenological approach to describe a community-based education program. The study found benefits to the community, including: developing partnership, increased awareness of services and sharing of resources.…”
Section: Theme 3: the Impact Of Community Nursing Education Programsmentioning
confidence: 99%
See 4 more Smart Citations
“…[6,8,36,53] Linda et al [8] used an interpretive existentialistphenomenological approach to describe a community-based education program. The study found benefits to the community, including: developing partnership, increased awareness of services and sharing of resources.…”
Section: Theme 3: the Impact Of Community Nursing Education Programsmentioning
confidence: 99%
“…[17] However, there is a need for students to be supported as they learn to become competent professionals, otherwise demoralisation and alienation from the community may result. [18] Furthermore, community nursing education as a pedagogical model [8] enables students to learn to provide nursing care for people no matter where they are encountered. Mtshali [6] noted that community-based programs are mainly employed where universities are in partnership with the community.…”
Section: Discusion Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations